Evaluation of a commercial packed bed flow hydrogenator for reaction screening, optimization, and synthesis - Bryan, Marian C.; Wernick, David; Hein, Christopher D.; Petersen, James V.; Eschelbach, John W.; Doherty, Elizabeth M. (Beilstein Journal of Organic Chemistry, 2011)
The performance of the ThalesNano H-Cube®, a commercial packed bed flow hydrogenator, was evaluated in the context of small scale reaction screening and optimization. A model reaction, the reduction of styrene to ethylbenzene through a 10% Pd/C catalyst bed, was used to examine performance at various pressure settings, over sequential runs, and with commercial catalyst cartridges. In addition, the consistency of the hydrogen flow was indirectly measured by in-line UV spectroscopy. Finally, system contamination due to catalyst leaching, and the resolution of this issue, is described. The impact of these factors on the run-to-run reproducibility of the H-Cube® reactor for screening and reaction optimization is discussed.
Keywords: catalyst leaching; CatCart®; H-Cube®; packed bed flow hydrogenation

(untitled) - Frost, C. G.; Mutton, L. (Green Chem., 2010)

(untitled) - Kobayashi, J.; Mori, Y.; Okamoto, K.; Akiyama, R.; Ueno, M.; Kitamori, T.; Kobayashi, S. (Science, 2004)

(untitled) - Yoswathananont, N.; Nitta, K.; Nishiuchi, Y.; Sato, M. (Chem. Commun., 2005)

(untitled) - O’Brien, M.; Taylor, N.; Polyzos, A.; Baxendale, I. R.; Ley, S. V. (Chem. Sci., 2011)

(untitled) - Jones, R. V.; Godorhazy, L.; Varga, N.; Szalay, D.; Urge, L.; Darvas, F. (J. Comb. Chem., 2006)

(untitled) - Jones, R.; Gödörházy, L.; Szalay, D.; Gerencsér, J.; Dormán, G.; Ürge, L.; Darvas, F. (QSAR Comb. Sci., 2005)

(untitled) - Knudsen, K. R.; Holden, J.; Ley, S. V.; Ladlow, M. (Adv. Synth. Catal., 2007)

(untitled) - Clapham, B.; Wilson, N. S.; Michmerhuizen, M. J.; Blanchard, D. P.; Dingle, D. M.; Nemcek, T. A.; Pan, J. Y.; Sauer, D. R. (J. Comb. Chem., 2008)

(untitled) - Irfan, M.; Petricci, E.; Glasnov, T. N.; Taddei, M.; Kappe, C. O. (Eur. J. Org. Chem., 2009)

(untitled) - Saaby, S.; Knudsen, K. R.; Ladlow, M.; Ley, S. V. (Chem. Commun., 2005)

(untitled) - Cserényi, S.; Szőllősi, G.; Szőri, K.; Fülöp, F.; Bartók, M. (Catal. Commun., 2010)

Elements of Chemical Reaction Engineering - Fogler, H. S. (Prentice Hall, 2005)

(untitled) - van Herk, D.; Castaño, P.; Quaglia, M.; Kreutzer, M. T.; Makkee, M.; Moulijn, J. A. (Appl. Catal., A, 2009)

(untitled) - van Herk, D.; Kreutzer, M. T.; Makkee, M.; Moulijn, J. A. (Catal. Today, 2005)

(untitled) - van Herk, D.; Castaño, P.; Makkee, M.; Moulijn, J. A.; Kreutzer, M. T. (Appl. Catal., A, 2009)

(untitled) - Glasnov, T. N.; Findenig, S.; Kappe, C. O. (Chem.–Eur. J., 2009)

(untitled) - Auer, E.; Freund, A.; Pietsch, J.; Tacke, T. (Appl. Catal., A, 1998)